Incidence of angiolymphatic invasion in colorectal cancer - Lopes,Renan Cascaes (2012)
Angiolymphatic invasion (ALI) in colorectal cancer (CRC) is considered as an important independent prognostic factor and may influence therapeutic decisions. OBJECTIVE: This aim of the study is to find the incidence of ALI in histopathological reports of surgical specimens from patients who underwent surgical treatment of colorectal adenocarcinoma. RESULTS: One hundred and twenty seven patients were male (50.6%) and the mean age was 60 years old. The overall incidence of ALI was 44.6%, and there was a significant association with age (p=0.016), lymph node involvement (N) (p<0.00001) and tumor differentiation (p=0.0039). CONCLUSION: There was a higher probability of finding ALI in younger patients, with a higher number of lymph node metastases and a lower tumor differentiation.